Diode laser materials & devices a worldwide market & technology overview to 2005 - Szweda, Roy
This report examines the development of the diode laser industry over a six-year period, 2000 to 2005, incorporating analysis of trends in markets, technologies and industry structure. It is designed to provide key information to users and manufacturers of substrates, epitaxial wafers (epiwafers) and devices. The coverage includes components, laser diodes, and the semiconducting (SC) wafers and epiwafers on which most of these devices are made. The geographical coverage of the report includes North America, Japan and Europe, which together will account for over 90% of the production and consum.